Thoughts on developing small/medium size no-till equipment for conservation agriculture in Asia: Summary of post-publication peer review comments - Jin, He; Hongwen, Li; Yingkuan, Wang; Zhiqiang, Zhang; Qingjie, Wang (International Journal of Agricultural and Biological Engineering, 2014)
Traditional agriculture bases most of its operations or practices on soil tillage, which causes likely occurrence of water and soil erosion and sediment runoff. In order to conserve soil, water and environment, Conservation agriculture (CA) is increasingly adopted to replace traditional tillage agriculture to achieve sustainable and profitable agriculture and subsequently improve the livelihoods of farmers. CA holds great potential for all sizes of farms and agro-ecological systems, but its adoption is most urgently required by smallholder farmers, especially those short of laborers. Small/medium size no-till machines and implements are the key to CA adoption. A review article on small/medium size no/minimum-till seeders in Asia published in IJABE triggers a lot of scientific conversation on how to develop suitable no-till equipment among peer experts. This paper presents a collection of these post-publication peer review comments including commentary, questions, answers, suggestions, critical thinking, etc. The authors of the review article also provide response, summary of the review comments and their own standpoints. This open post-publication review and commentary may add value to the published review article and provide new ideas useful for future research and development of CA equipment.Keywords: conservation agriculture, conservation tillage, no-till equipment, post-publication peer reviewDOI: 10.3965/j.ijabe.20140705.16Citation: He J, Li H W, Wang Y K, Zhang Z Q, Wang Q J. Thoughts on developing small/medium size no-till equipment for conservation agriculture in Asia: Summary of post-publication peer review comments. Int J Agric & Biol Eng, 2014; 7(5): 139－146.